2021
DOI: 10.3390/su13169039
|View full text |Cite
|
Sign up to set email alerts
|

Product Design for Automated Remanufacturing—A Case Study of Electric and Electronic Equipment in Sweden

Abstract: Remanufacturing is one of the main practices toward a circular economy and industrial sustainability. Remanufacturing is highly dependent on how circular products are designed and developed. Remanufacturing can also benefit from automation for efficiency, accuracy and flexibility. This paper, via a multiple case study, connects the three areas of remanufacturing, product design and automation and investigates how circular product design can facilitate automation remanufacturing processes. First, circular produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…More specifically, our study contributes to knowledge accumulation on the topic, since while a number of studies involved WMs, most of them did not provide quantitative environmental analyses, and even fewer based them on real consumers data (such as [29,30], and other studies mentioned in [63]). The same is found by this study on the role of refurbishment, which already received considerable attention in the literature as a circular economy strategy [22,64,65], and also specifically for WMs [66]. While several studies focused on product design [9,67], however, our study considers the potential of the current WM installed base to be cost-and environmentally effective with a refurbishment business model.…”
Section: Discussionsupporting
confidence: 71%
“…More specifically, our study contributes to knowledge accumulation on the topic, since while a number of studies involved WMs, most of them did not provide quantitative environmental analyses, and even fewer based them on real consumers data (such as [29,30], and other studies mentioned in [63]). The same is found by this study on the role of refurbishment, which already received considerable attention in the literature as a circular economy strategy [22,64,65], and also specifically for WMs [66]. While several studies focused on product design [9,67], however, our study considers the potential of the current WM installed base to be cost-and environmentally effective with a refurbishment business model.…”
Section: Discussionsupporting
confidence: 71%
“…However, it is a matter of case-to-case as remanufacturing challenges are commonly company-specific (Lundmark et al, 2009). For example, on the one hand, the case study by Shahbazi et al (2021) showed automation as an enabler for flexible remanufacturing processes, given that products were designed for remanufacturing. On the other hand, Sakao and Sundin (2019) and Sundin et al (2020) exemplified successful cases of automated remanufacturing but also highlighted the inherent uncertainty of remanufacturing as a barrier to automation.…”
Section: Remanufacturing Process and Technologymentioning
confidence: 99%
“…Another example is automated remanufacturing, as covered in Subchapter 4.1.1. Automation can be challenging but also, given the right circumstances, beneficial in terms of creating an efficient and effective process (Sakao and Sundin, 2019;Shahbazi et al, 2021).…”
Section: Remanufacturing Process Improvementsmentioning
confidence: 99%
“…Although users can make decisions based on previous experience, this type of decision-making method needs a long-term accumulation of experience. Accordingly, there is no guarantee to use the optimal configuration as the selected remanufacturing scheme [ 4 , 5 ]. Meanwhile, since the expenses of electronic control systems for remanufacturing are higher than one million yuan, bad decisions will lead to economic losses.…”
Section: Introductionmentioning
confidence: 99%